Ecoprint Creations as Artistic Eco-Friendly Interior Accessories - Ponimin, Ponimin; Ratnawati, Ike; Asmi Nusantari, Okta Viviana; Abhista Rozi, Eldiza Elmira (Gondang: Jurnal Seni dan Budaya, 2025)
The development of aesthetic products for interior accessories has evolved with a variety of designs and materials. Interior accessories based on local potential and eco-friendly products are the hopes of any society in the era of increasing awareness of eco-friendly lifestyles. This research aims to create interior accessory products with local natural plant growth materials through the use of ecoprint textile crafts as a basis for the development. To realise this aim, a creative art method is necessary. These methods include: (a) product design, (b) preparation of materials and techniques, (c) the process of making ecoprint decorative motifs on fabrics, (d) application of ecoprint fabrics combined with other materials as surface decoration of prospective interior accessory element products, (d) finishing of prototype interior accessory element products from the combination of ecoprint, (e) analysis of creative results of the developed interior aesthetic element products. The products of this project consist of hanging lampshade, sitting lamp, and table ware products. It is expected that the results of this creation can enrich the variety of eco-friendly-based interior accessories craft products, which are developed from local potential.